Role of religion, spirituality, and faith in assisted reproduction - Daniela Paes de Almeida Ferreira Braga; Rose Marie Massaro Melamed; Amanda Souza Setti; Bianca Ferrarini Zanetti; Rita de Cássia Sávio Figueira; Assumpto Iaconelli; Edson Borges (Taylor & Francis Group, 2019)
Purpose: The purpose of this study is to evaluate the impact of the patient's faith, religion, and spirituality on the outcomes of intracytoplasmic sperm injection (ICSI) cycles. Materials and methods: Eight hundred and seventy-seven patients received a questionnaire containing information on faith, religiosity, and spirituality and the results of the questionnaires were correlated with ICSI outcomes. Patients stated to be Catholic (n = 476), spiritists (n = 93), Evangelical (n = 118), and other religion (n = 32), and 78 did not identify with any religious group. Results: A significant increase in fertilization, high-quality embryos, and pregnancy rate was found among Spiritists and Evangelicals. Patients who included the infertility diagnosis and treatment in their prayers showed an increased pregnancy rate, and those who reported their faith to be affected by the infertility diagnosis presented a decreased high-quality embryos rate. The high-quality embryos rate was increased among patients who answered that their faith contributed to their decision to undergo infertility treatment. The cycle's cancelation was negatively correlated with the frequency of religious meetings, and the frequency of prayers was positively correlated with the response to ovarian stimulation. Finally, belief in treatment success positively influenced the embryo quality. Conclusion: The findings suggest that spirituality plays a role in adjusting the psychological aspects of an infertile patient.